The relative effectiveness of two instructional approaches in teaching division involving zero - Padua, Felix C. 1950- (1977)
The study aimed to determine the relative effectiveness of two instructional approaches, specifically the multiplication division approach (M-D) and the division multiplication approach (D-M), in teaching mathematical division involving zero to grades five, six, and first year high school students. A pretest, posttest, and a retention test were constructed similarly with 18 items each. The study was conducted over three school days. The results of the three tests across the three grade levels were then analyzed using covariance. It was concluded from the results that the D-M approach students performed better than those taught using the M-D approach in the posttest; however, their performance in the retention test conducted six weeks after the division lesson was not as good. In this last test, there was no significant difference in the performance of the two groups of students.
December, 1977.
Vita.
Thesis (M.A.T. Elementary Mathematics)--University of the Philippines, Diliman.
Keywords: Division -- Study and teaching (Elementary) -- Philippines; Division -- Study and teaching (Secondary) -- Philippines; Zero (The number)